2009
DOI: 10.1159/000208794
|View full text |Cite
|
Sign up to set email alerts
|

Fetal Reversed Constrictive Effect of Indomethacin and Postnatal Delayed Closure of the Ductus Arteriosus following Administration of Transplacental Magnesium Sulfate in Rats

Abstract: Background: Magnesium sulfate (MgSO4) is used therapeutically for eclampsia and tocolysis. Some reports have suggested a relationship between therapeutic MgSO4 and patent ductus arteriosus (DA) in preterm infants. Objectives: To clarify patent DA induction by MgSO4 in preterm infants, we studied the increase in serum Mg concentrations and fetal dilatation and postnatal delayed closure of the ductus, using transplacental MgSO4 in rats. Methods: Fetal and neonatal duct… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
4
0

Year Published

2010
2010
2019
2019

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 37 publications
1
4
0
Order By: Relevance
“…As previously demonstrated in a 2009 animal study, hypermagnesemia induced by transplacental magnesium sulfate attenuated the fetal ductus-constricting effects of indomethacin and delayed postnatal ductal closure in rats [5]. This phenomenon has also been reported in extremely preterm neonates in which antenatal magnesium sulfate treatment has been associated with a greater frequency of DA patency and reduced clinical responsiveness of the DA to indomethacin therapy [6,7].…”
Section: Discussionsupporting
confidence: 64%
See 1 more Smart Citation
“…As previously demonstrated in a 2009 animal study, hypermagnesemia induced by transplacental magnesium sulfate attenuated the fetal ductus-constricting effects of indomethacin and delayed postnatal ductal closure in rats [5]. This phenomenon has also been reported in extremely preterm neonates in which antenatal magnesium sulfate treatment has been associated with a greater frequency of DA patency and reduced clinical responsiveness of the DA to indomethacin therapy [6,7].…”
Section: Discussionsupporting
confidence: 64%
“…We defined DA constriction as a PI ≤1.94 [3], and quantified DA constriction as severe (PI ≤1.0) or mild-to-moderate constriction (PI > 1.0 and ≤1.94) (Figure 1). We used the PI to determine the severity of DA constriction, as it remains constant despite changes in gestational age [3] and is relatively angle independent [5].…”
Section: Fetal Hemodynamic Datamentioning
confidence: 99%
“…Some studies reported dilation of foetal ductus arteriosus following maternal administration of phosphodiesterase 3 or 5 inhibitor, and magnesium sulphate in rats. [14][15][16] These agents dilated constrictive ductus arteriosus by indomethacin in foetal rats, suggesting the potential usefulness of maternal administration of these agents for the treatment of idiopathic or secondary foetal ductal narrowing. Patients having right ventricular outflow tract obstruction with foetal ductal narrowing may need maternal administration of these agents for the treatment and prophylaxis of constrictive ductus arteriosus.…”
Section: Discussionmentioning
confidence: 99%
“…Mg 2+ , a natural calcium channel blocker, administered antenatally as MgSO 4 , results in a dose-dependent delayed DA closure and a higher incidence of PDA. [130][131][132][133][134] This effect seems to be short, since the responsiveness to postnatal INDO prophylaxis is reduced while the symptomatic treatment in a later phase is not influenced. 132 The only report on antenatal use of a calcium channel blocker, nifedipine, did not find a higher prevalence of PDA.…”
Section: The Effect Of Ante-or Postnatal Exposure To Various Medicatimentioning
confidence: 99%